2013
DOI: 10.1175/jcli-d-12-00616.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Gradients in Aerosol-Induced Atmospheric Heating and Surface Dimming over the Oceanic Regions around India: Anthropogenic or Natural?

Abstract: Making use of the extensive shipboard and aircraft measurements of aerosol properties over the oceanic regions surrounding the Indian peninsula, under the Integrated Campaign for Aerosols, gases and Radiation Budget (ICARB) field experiment during the premonsoon season (March-May), supplemented with longterm satellite data and chemical transport model simulations, investigations are made of the east-west and north-south gradients in aerosol properties and estimated radiative forcing, over the oceans around Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Due to lack of long‐term spectral measurements of single‐scattering albedo (SSA) and phase function over Bay of Bengal, we have used a semiempirical approach in which the SSA and phase function are estimated by iterating the number concentration of the aerosol components adopted from Koepke et al () (OPAC) in such a way that the estimated aerosol parameters matches well with the measured aerosol parameters as discussed in section 2.3. When the optical properties estimated using the model matches well with the measured aerosol properties, we adopt that aerosol composition to estimate spectral variation of AOD, SSA, and asymmetry parameter required for the radiative transfer calculations (Moorthy et al, ; Nair, Babu, et al, ). For the estimation of dust radiative forcing, dust optical depth obtained at 532 nm and vertical profile of dust extinction coefficient derived using CALIOP depolarization measurements are used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to lack of long‐term spectral measurements of single‐scattering albedo (SSA) and phase function over Bay of Bengal, we have used a semiempirical approach in which the SSA and phase function are estimated by iterating the number concentration of the aerosol components adopted from Koepke et al () (OPAC) in such a way that the estimated aerosol parameters matches well with the measured aerosol parameters as discussed in section 2.3. When the optical properties estimated using the model matches well with the measured aerosol properties, we adopt that aerosol composition to estimate spectral variation of AOD, SSA, and asymmetry parameter required for the radiative transfer calculations (Moorthy et al, ; Nair, Babu, et al, ). For the estimation of dust radiative forcing, dust optical depth obtained at 532 nm and vertical profile of dust extinction coefficient derived using CALIOP depolarization measurements are used.…”
Section: Resultsmentioning
confidence: 99%
“…Details on the retrieval process are given by Ackerman et al () and Remer et al (). Extensive comparison of MODIS level 3 aerosol optical depth (AOD) data (at 0.55 μm) with 171 days of ship‐borne Sun photometer measurements over oceanic regions surrounding the Indian peninsula during 2003–2010 showed good agreement with a correlation coefficient of 0.91 and slope of 0.95 (Nair, Babu, et al, ). The present study made use of level 3 MODIS collection 6 (MYD08_M3) QA weighted data product over the ocean to obtain aerosol optical depth over the study region (Levy et al, ).…”
Section: Data Set and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the observed increasing trend in Arabian dust activity on the interannual to decadal timescale variations in the Indian summer monsoon rainfall has revealed dynamical and positive feedback due to dust‐induced diabatic heating over the region [ Solmon et al ., ]. This is in line with the meridional and zonal gradients in the aerosol‐induced atmospheric heating rate in the lower free troposphere estimated based on extensive ship‐borne and satellite measurements made over the region [ Nair et al ., ]. The study confirmed that aerosol‐induced gradients (meridional and zonal) in surface cooling and atmospheric warming are mostly anthropogenic in origin [ Nair et al ., ].…”
Section: Aerosols and Climate Change In Asia: An Observational Perspementioning
confidence: 99%
“…Synthesizing the cruise measurements with those from the network and data from lidars, Nair et al 71 have shown large zonal and meridional gradients in the aerosol induced lower atmospheric heating rate across Indian Peninsula; from 0.5 K d -1 at 55E (over western Arabian Sea) increasing to 1.5 K d -1 over eastern BoB (100E) with contrasting meridional gradient on either side of the peninsula.…”
Section: Icarbmentioning
confidence: 99%